Pengenalan Hukum Tajwid Dan Pembelajaran Tahsin Al Qur’an Dengan Metode Al Bayan Dan Qira’ati Di TPA Darul Falah Dusun Kunaiyan KKN Desa Hurun - Muhammad Fajar; Shelvia Loviana; Arizal Eka Putra; Akhmad Fadillah Isnan; Rahmat Hidayat; Muhammad Fakhrul Razi Khova (STIKes Ibnu Sina Ajibarang, 2023)
This research is motivated by the large number of children today, especially in rural areas, where there are still children who cannot read the Qur'an according to the knowledge of tajwid and tahsin. If from an early age you are still unable to read the Al-Qur'an using the knowledge of tajwid and tahsin, then it will also be difficult when you grow up to understand the laws of reading in the Al-Qur'an. Therefore, many parents entrust their children to the Al-Quran Education Park (TPA) to learn religion, especially how to read the Al-Quran. However, this is still not optimal because some of the teachers there do not apply the science of tajwid and tahsin, so KKN students teach tajwid and tahsin lessons. Namely using a method to make it easier for children to read the Koran, namely the Al Bayan and Qira'ati methods. The aim of this research is to determine the implementation of the Al Bayan and Qira'ati methods, as well as the factors that support and inhibit learning to read the Koran. This type of research uses qualitative research. Data collection techniques use observation. The data analysis technique used is descriptive interpretive. The research results show that the Qira'ati method can be applied in this village, because using this method is able to attract children to diligently read the Al-Qur'an and also so that children do not feel bored when learning to read the Al-Qur'an. Factors that support learning the Koran are (a) Place; and (b) Learning Media. Then the factors that inhibit it are facilities and infrastructure